2018
DOI: 10.1093/cid/ciy826
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal and Legionella Urinary Antigen Tests in Community-acquired Pneumonia: Prospective Evaluation of Indications for Testing

Abstract: Background Adult, community-acquired pneumonia (CAP) guidelines from the Infectious Diseases Society of America (IDSA) and American Thoracic Society (ATS) include indications for urinary antigen tests (UATs) for Streptococcus pneumoniae (SP) and Legionella pneumophila (LP). These recommendations were based on expert opinions and have not been rigorously evaluated. Methods We used data from a multicenter, prospective, surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…Endotracheal aspirates are more likely to recover the causative organism than expectorated sputum, and organisms recovered immediately after intubation is unlikely to reflect mere colonization; in patients with malignancies and ARF, a randomized-controlled trial reported that a strategy with non-invasive testing only (including sputum sampling) was not inferior to FOB/BAL [5]. In patients admitted for CAP, urine antigen detection was 61% sensitive and 39% specific for S. pneumoniae, and corresponding values for L. pneumophila were 63% and 35% [34]. Blood cultures also have low yields of 5-14% in patients admitted for CAP [5,35], although higher yields have been reported when the pulmonary involvement was severe.…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
“…Endotracheal aspirates are more likely to recover the causative organism than expectorated sputum, and organisms recovered immediately after intubation is unlikely to reflect mere colonization; in patients with malignancies and ARF, a randomized-controlled trial reported that a strategy with non-invasive testing only (including sputum sampling) was not inferior to FOB/BAL [5]. In patients admitted for CAP, urine antigen detection was 61% sensitive and 39% specific for S. pneumoniae, and corresponding values for L. pneumophila were 63% and 35% [34]. Blood cultures also have low yields of 5-14% in patients admitted for CAP [5,35], although higher yields have been reported when the pulmonary involvement was severe.…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
“…Other authors have found similar rates of positive test prevalence: between 5.2% and 8.8% in ward-based patients and 15% of those requiring intensive care [18,23,24]. The low rate of positive UAT results in over 90% of tests yielding negative results [18,22,23] and these do not contribute to clinical management as the low sensitivity of UAT means a negative test result cannot exclude infection with S. pneumoniae.…”
Section: Clinical Usage and Impactmentioning
confidence: 81%
“…A recent large prospective study found that patients who met IDSA/ATS guidelines for pneumococcal UAT infrequently had a positive result on testing (a positive test prevalence of 4.2%) [22], demonstrating that current testing indications have poor sensitivity and specificity in identifying patients with positive pneumococcal urinary antigen. Other authors have found similar rates of positive test prevalence: between 5.2% and 8.8% in ward-based patients and 15% of those requiring intensive care [18,23,24].…”
Section: Clinical Usage and Impactmentioning
confidence: 99%
“…Current guidelines do not recommend routine Legionella testing since empirical treatment regimens for pneumonia generally include antibiotics with anti-Legionella activity [11], and testing in low-risk settings may not be cost-effective [18]. In regions that are endemic for Legionella, however, systematic testing identifies cases that would otherwise remain undetected [12,14,19], facilitates targeted antibiotic therapy, and serves a public health function as surveillance for potential outbreaks. Rapid, accessible microbiologic methods are more sensitive and specific than any scoring algorithm and may be easier to use as a screening method than a complex score requiring multiple tests not typically sent on non-critically ill pneumonia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, current guidelines do not recommend routine testing for Legionella [11]. Rather, targeted testing of healthcare and severe community-acquired pneumonias is recommended-an approach that misses a significant percentage of Legionella cases [12]. Therefore, studies of Legionella pneumonia have artifactual biases toward more severe cases and presentations with conventionally attributed symptoms.…”
Section: Introductionmentioning
confidence: 99%